A novel ferroelectric nanopillar multi-level cell memory. (February 2023) - Lee, Hyeongu; Shin, Mincheol
Abstract: In this work, we present a novel multi-level non-volatile memory (NVM) device where ferroelectric (FE) nanopillars are embedded in a dielectric (DE) medium. Using our in-house 3D phase field simulator developed to treat the FE–DE composite system stably, we demonstrate that n FE nanopillars can generate more than 2 n states, enabling high storage capacity. The multistates of the pillar array device are attributed to the depolarization field modulation with the pillar height and the multi-domain topological states of nanoscale FE structures. Highlights: n -ferroelectric nanopillars embedded in dielectric medium can show more than 2 n states. Depolarization field engineering by modulating the pillar height results in multi-level switching. Long-range Coulomb interaction between the nanopillars affects the accessible topological states.